Pandan leaves extract (Pandanus amaryllifolius Roxb) as a food preservative - Resmi Aini; Ana Mardiyaningsih (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background : Food poisoning or foodborne disease is still a serious concern in Indonesia. The use of harmful synthetic chemical preservatives are still widely found in society. Therefore, it would require efforts to develop safe natural preservatives― for instance, from Pandan leaves (Pandanus amayllifolius Roxb) which are often used as a natural food coloring and flavor concentrates, and has also widely known to have anti-bacterial activities. Objective : This study aims to determine the potential of pandan leaves extract (Pandanus amaryllifolius Roxb) in lowering the total plate count and the number of mold on traditional food. Methods : After making the water of pandan leaves extract, a phytochemical test was done to determine bioactive compounds, such as tannin, alkaloids, flavonoids, and polyphenols which has anti-microbial properties. In order to determine its food preservatives capabilities, Total Plate Count and Number of Mold was used on a traditional food called Putu Ayu. Results : Pandan leaves extract contain bioactive compound like tannin, alkaloids, flavonoids, and polyphenols. There were no colonization found in Putu Ayu that was added 15% pandan leaves extract concentration in 101 dilution. The result of Number of Mold Count of Putu Ayu that contain 15% pandan leaves extract concentration showed no mold growth in 104 dilution but failed to provide good fragarance and flavor in food products. Conclusion : Pandan leaves extract in the concentration of 15% were able to decrease Total Plate Count and Number of Mold in traditional food.